Sequential Anti-PD1 Therapy Following Dendritic Cell Vaccination Improves Survival in a HER2 Mammary Carcinoma Model and Identifies a Critical Role for CD4 T Cells in Mediating the Response - Kodumudi, Krithika N.; Ramamoorthi, Ganesan; Snyder, Colin; Basu, Amrita; Jia, Yongsheng; Awshah, Sabrina; Beyer, Amber P.; Wiener, Doris; Lam, Lian; Zhang, Hongtao; Greene, Mark I.; Costa, Ricardo L. B.; et al. (Frontiers in Immunology, 2019)
Patients with metastatic HER2 breast cancer (MBC) often become resistant to HER 2 targeted therapy and recur. The Panacea trial suggested that HER2 MBC patients were more likely to respond to checkpoint therapy if TIL were present or if tumor expressed PD-L1. We assessed whether type I polarized dendritic cells (DC1) could improve checkpoint therapy in a preclinical model of HER2+ breast cancer. TUBO bearing mice were vaccinated with either MHC class I or class II HER2 peptide pulsed DC1 (class I or class II HER2-DC1) concurrent or sequentially with administration of anti-PD-1 or anti-PDL1. Infiltration of tumors by immune cells, induction of anti-HER2 immunity and response to therapy was evaluated. Both Class I or class II HER2- DC1 vaccinated mice generated anti-HER2 CD8 or CD4+ T cell immune responses and demonstrated delayed tumor growth. Combining both MHC class I and II HER2-pulsed DC1 did not further result in tumor growth inhibition or enhanced survival compared to individual administration. Interestingly class II HER2- DC1 led to both increased CD4 and CD8 T cells into the tumor microenvironment while class I peptides typically resulted in only increased CD8 T cells. Anti-PD-1 but not anti-PD-L1 administered sequentially with HER2-DC1 vaccine could improve the efficacy of HER2-DC1 vaccines as measured by tumor growth, survival, infiltration of tumors by T cells and systemic anti-HER2 immune responses. Depletion of CD4+ T cells abrogated the anti-tumor efficacy of combination therapy with class II HER2-DC1 and anti-PD-1 suggesting that tumor regression was CD4 dependent. Since class II HER2-DC1 were as effective as class I, we combined class II HER2- DC1 vaccines with anti-rat neu antibodies and anti-PD-1 therapy. Combination therapy demonstrated further delay in tumor growth, and enhanced survival compared to control mice. In summary, Class II HER2- DC1 drives both a CD4 and CD8 T cell tumor infiltration that leads to increased survival, and in combination with anti-HER2 therapy and checkpoint blockade can improve survival in preclinical models of HER2 positive breast cancer and warrants exploration in patients with HER2 MBC.